2006
DOI: 10.1016/j.jacc.2005.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Serial Angiographic Follow-Up of Sirolimus-Eluting Stents for Unprotected Left Main Coronary Artery Revascularization

Abstract: Restenosis is a frequent finding when serial angiographic follow-up is performed after SES implantation for unprotected distal LMCA lesions. Restenosis is usually focal, most often involves the LCX ostium, and often occurs without symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
133
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(147 citation statements)
references
References 21 publications
9
133
2
3
Order By: Relevance
“…[4][5][6][7][8][9][10]15 In our study isolated LMS did not occur, but LMS was associated with non-critical CAD in 8 patients (7.8%). So, our results were similar to international studies regarding involvement of LMS with multivessel CAD and predominance of distal vessel involvement.…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…[4][5][6][7][8][9][10]15 In our study isolated LMS did not occur, but LMS was associated with non-critical CAD in 8 patients (7.8%). So, our results were similar to international studies regarding involvement of LMS with multivessel CAD and predominance of distal vessel involvement.…”
Section: Discussioncontrasting
confidence: 39%
“…[3][4][5][6][7][8][9][10] In our study location of the lesion was distal in 70 (68.6%) patients.In a study by Saeed Sadeghian et al showed that the proportion of the male sex in those with LMS was higher than that of the ones without LMS stenosis (87.8% vs. 71.4%, P=0.020) and that patients with LMS stenosis were older (mean age of 58.8±10.5 years in those with LMS stenosis vs. 55.6±9.2 in the ones without LMS, P=0.03).…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Apart from being technically challenging with the use of two stents, the long-term outcome have also been reported to be less favourable, and inconsistent. [10][11][12] Target lesion revascularisation (TLR) and target vessel revascularisation (TVR) ranged from 2% to 38% and cardiac mortality from 0% to 11%. 10 A single centre retrospective observational study reported 5% incidence of in-hospital complication with use of DES in unprotected LMCA disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, the story has been different for bifurcation lesions with several studies showing LMCA distal bifurcation lesions as unfavorable settings for percutaneous intervention due to lower procedural success and higher restenosis rates. 15 -17 To site 1 example, Price et al 18 published data on 50 patients with 94% of distal bifurcation lesions and 9 months follow-up; MACE rate was 10% in-hospital and 44% at 9 months with an overall angiographic restenosis rate of 42%.…”
Section: Discussionmentioning
confidence: 99%